Rural-urban migration around Yangon city, Myanmar - Htoo, Kyan; Zu, A Myint (Michigan State University, 2018)
Rural-urban migration has increased dramatically since 2010 in the area around Myanmar’s largest commercial center, Yangon, where it represents a far more important migration flow than international migration.